Beginning ASP.NET 4.5 in C# - MacDonald, Matthew; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
This book is the most comprehensive and up to date introduction to ASP.NET ever written. Focussing solely on C#, with no code samples duplicated in other languages, award winning author Matthew MacDonald introduces you to the very latest thinking and best practices for the ASP.NET 4.5 technology. Assuming no prior coding experience, you'll be taught everything you need to know from the ground up. Starting from first principals, you'll learn the skills you need to be an effective ASP.NET developer who is ready to progress to more sophisticated projects and professional work. You'll be taught how to use object orientation and code-behind techniques to lay out your code clearly in a way other developers can easily understand. You'll learn how to query databases from within you web pages, spice up your layouts using ASP.NET AJAX and deploy your finished websites to production servers. You'll also learn how to debug your code when things go wrong and the performance and scalability issues that can affect your web projects as they grow. With you book you can take your first step towards becoming a successful ASP.NET developer with confidence.
Keywords: Computer science; Computer Science; Computer Science, general